2012
DOI: 10.1007/s10853-012-6625-6
|View full text |Cite
|
Sign up to set email alerts
|

Stress corrosion cracking susceptibility of ultrafine grained AZ31

Abstract: In this study, stress corrosion cracking (SCC) behavior of AZ31 magnesium alloy was carried out using slow strain rate testing (SSRT) technique in 3.5 wt% NaCl solution. The influence of microstructural scale on the stress corrosion behavior was investigated in AZ31 alloy with three different mean grain sizes. Single-pass and two-pass friction stir processing (FSP) was employed to obtain fine grain and ultrafine grain microstructures, respectively. For FSP, SSRT specimens were extracted from the processed regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Most of UFG materials in the list are pressed by ECAP, HPT, ARB as the core of SPD technology, but the recent emerging SPD for surface modi cation such as surface mechanical attrition treatment (SMAT), 21,[72][73][74] cryorolling, 75,76) high-power shotblast, [77][78][79][80][81] burnishing, [82][83][84] friction stir processing (FSP) 85,86) are included. However, nanocrystalline metals, which are fabricated by the so-called bottom-up approaches such as magnetron and DC spattering, powder consolidation by high-energy ball milling are excluded in this Better=Corrosion resistance increases with grain size reduction, Worse=Vise versa.…”
Section: Introductionmentioning
confidence: 99%
“…Most of UFG materials in the list are pressed by ECAP, HPT, ARB as the core of SPD technology, but the recent emerging SPD for surface modi cation such as surface mechanical attrition treatment (SMAT), 21,[72][73][74] cryorolling, 75,76) high-power shotblast, [77][78][79][80][81] burnishing, [82][83][84] friction stir processing (FSP) 85,86) are included. However, nanocrystalline metals, which are fabricated by the so-called bottom-up approaches such as magnetron and DC spattering, powder consolidation by high-energy ball milling are excluded in this Better=Corrosion resistance increases with grain size reduction, Worse=Vise versa.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, grain boundaries, as a kind of crystal defect, stored high energy as well and exhibited unfavourable impact on corrosion resistance to some extent. Diffusion of hydrogen prone to grain boundaries and diffusivity will be accelerated with the increased proportion of grain boundaries per volume of refined microstructure [9].…”
Section: Discussionmentioning
confidence: 99%
“…However, a conclusion about the effect of grain refinement on SCC has not yet been reached in the limited literature. Argade et al [9] reported that ultrafine grained AZ31 processed by friction stir processing, one of the SPD methods, exhibited higher susceptibility to SCC because of the enhanced hydrogen diffusivity. Lopez et al [10] claimed that an austenitic stainless steel containing 0.97 wt % nitrogen achieved higher resistance to SCC through grain refinement compared to the as-received steel in 30% NaCl solution at 90 • C.…”
Section: Introductionmentioning
confidence: 99%
“…Argade et al [8] studied the mechanism of AZ31 Mg alloy under slow strain rate testing technique. They found that the corrosion of AZ31 is predominantly influenced by its microstructure which results in a favorable texture for increased adsorption of hydrogen.…”
Section: Introductionmentioning
confidence: 99%